(untitled) (AYUSHDHARA, 2025)
Primary infertility is defined as the inability to conceive after one year of unprotected intercourse, without any prior pregnancies. Unexplained infertility accounts for nearly 15–30% of cases, where no identifiable cause can be detected despite standard investigations. The current case study explores the Ayurvedic approach to manage unexplained primary infertility. Case Presentation: A 24-year-old nulligravida female presented with a 4-year history of primary infertility and scanty menstruation, despite normal findings in ovulation and her husband’s semen analysis. Clinically, she had a BMI of 18.4 and exhibited signs of Artava Kshaya and Dhatu Kshaya, indicating Vata aggravation and nutritional insufficiency. Intervention and Management: A comprehensive Ayurvedic treatment protocol was initiated, including Samana and Shodhana therapies. Yoga Basti using Dashmoola was administered to pacify Vata and restore reproductive balance. Shatapushpa was used for its Artavajanana properties, along with nourishing Rasayana herbs like Ashwagandha, Shatavari, Vidarikanda, and Bala. Phala Ghrita was prescribed to stabilize the uterus and enhance fertility. Nutritional correction and Nidana Parivarjana were emphasized, alongside Beeja Sanskara and lifestyle guidance. Outcome: After the course of treatment, the patient’s menstrual flow normalized, BMI improved and hormonal balance was restored. A follicular study confirmed timely ovulation. Ultimately, the patient conceived, confirmed by a positive urine pregnancy test. Conclusion: This case demonstrates the effectiveness of individualized Ayurvedic management in addressing unexplained primary infertility. The approach, focusing on Vata Shamana, Dhatu Poshana led to successful conception. Ayurveda offers a promising alternative in cases where conventional diagnostics fail to identify a cause.